2016
DOI: 10.1002/jwmg.21095
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection by female moose in the Canadian prairie ecozone

Abstract: The combined effects of global climate change and shifting patterns in land use have resulted in range shifts for many wildlife species, as favorable conditions have been created for species entering novel environments. Moose (Alces alces) are a forest specialist species but have recently expanded southward from their traditional range in the boreal and aspen parkland forests into the agriculture-dominated landscape of the Prairie Pothole Region in western Canada. We quantified habitat selection patterns for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Moose populations have even expanded into some regions of their range (Wattles and DeStefano , ; Murray et al ; DeCesare et al ; Timmerman and Rodgers ). Southward expansions into the Prairie Pothole Region of Saskatchewan, Canada, for example, may be a result of expanding wetlands that can be used for thermoregulation (Laforge et al ). A more recent study, however, suggested that expansions were most likely the result of colder and dryer winters associated with the North Atlantic Oscillation (NAO) and greater coverage of high‐protein crops (Laforge et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Moose populations have even expanded into some regions of their range (Wattles and DeStefano , ; Murray et al ; DeCesare et al ; Timmerman and Rodgers ). Southward expansions into the Prairie Pothole Region of Saskatchewan, Canada, for example, may be a result of expanding wetlands that can be used for thermoregulation (Laforge et al ). A more recent study, however, suggested that expansions were most likely the result of colder and dryer winters associated with the North Atlantic Oscillation (NAO) and greater coverage of high‐protein crops (Laforge et al ).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that wetland abundance in the Canadian prairies may not be a limiting factor for moose (at least not over the timescale of this study), despite strong evidence from Laforge et al . 10 who found that at a fine scale (100 m) moose in agricultural systems select for wetlands in both summer and winter. This is likely explained by the widespread distribution of Prairie Pothole wetlands across the landscape such that they are widely available throughout most of our study area and locally selected by moose at fine scales.…”
Section: Discussionmentioning
confidence: 99%
“…Moose ( Alces alces ), are widely considered to be a boreal species with a circumpolar distribution 7 , 8 . However, over the past ~30 years, moose have become widespread across agricultural regions in the Boreal Plains and Prairie ecozones of Western Canada, areas typically considered highly unsuitable moose habitat and where transient animals were historically observed extremely rarely 9 , 10 . To understand ultimate causes for the encroachment of a species into a novel habitat, it is crucial to understand proximal causes underlying shifts in local distribution over larger scales.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations